Desain Perlindungan Hukum Pada Pelayanan Perizinan Berbasis Standar Pelayanan Partisipatif Satu Pintu - Sirajuddin Sirajuddin (Universitas Widya Gama Malang, 2022)
The Constitution guarantees the right for services, so that the government is obliged to provide protection guarantee and legal certainty to each citizen in the government and public services. Ironically, the right for services is often taken away by the egoism of the state elites and the fading professionality among the government apparatus as the providers of services. Therefore, it is interesting to study a proper design of legal protection to the license service recipients based on one-stop participatory licensing service standard after the enactment of the Law on Job Creation. This study employed a juridical normative approach. The results showed that the legal protection to the citizens in providing the licenses is still covered by cost uncertainty, service time, and low satisfaction among the citizens to the licensing service. As a result, it needs a strategy to strengthen the fulfillment of right for services by encouraging changes regulations into responsive and progressive ones with transparency and professionality of service and accompanied by cultural formation among the service apparatus ending in the legal protection to the licensing service recipients so that one-stop participatory service standard may be attained